1987
DOI: 10.1093/eurheartj/8.suppl_l.91
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacology of two specific bradycardic agents

Abstract: The effect of two i.v.-infusion regimens of falipamil on atropine-induced changes of heart rate and the effect of ULFS 49 Cl in 3 different oral doses during a 7-day medication period were studied in volunteers. Both studies were double-blind, randomized and placebo controlled. Under placebo, low doses of atropine caused a 16% reduction in heart rate, a 1 mg cumulative dose increased heart rate by 23%. 100 mg falipamil was followed by a 9% reduction in heart rate. Low doses of atropine enhanced this decrease t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
2

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 0 publications
1
13
0
2
Order By: Relevance
“…As shown in Fig.·2, a dose of zatebradine of 2.79±0.47·mg·l -1 decreased heart rate by half the maximum change, which compares well with similar experiments in mammals (Franke et al, 1987;Kalman et al, 1995;Ryu et al, 1996;Schipke et al, 1991). Thus, zatebradine is also a bradycardic agent in trout, indicating that the hyperpolarization current (If) is also a component of the pacemaker currents in nodal cells in this species.…”
Section: Zatebradine Is a Suitable Bradycardic Agentsupporting
confidence: 87%
“…As shown in Fig.·2, a dose of zatebradine of 2.79±0.47·mg·l -1 decreased heart rate by half the maximum change, which compares well with similar experiments in mammals (Franke et al, 1987;Kalman et al, 1995;Ryu et al, 1996;Schipke et al, 1991). Thus, zatebradine is also a bradycardic agent in trout, indicating that the hyperpolarization current (If) is also a component of the pacemaker currents in nodal cells in this species.…”
Section: Zatebradine Is a Suitable Bradycardic Agentsupporting
confidence: 87%
“…12 Because of the discrepancy between pharmacokinetic data and clinical efficacy, it was suggested that the tissular concentration rather than the plasma level of zatebradine is relevant. 13 Under this assumption, the zatebradine-induced, use-dependent block of hKv1.5 channels could become of clinical relevance, since even at heart rates slower than the normal sinus rhythm (0.5 Hz), zatebradine is able to inhibit the hKv1.5-like current and thus prolong the action potential duration, probably with a K D value similar to that necessary to inhibit the I f in a use-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…"2 Heart rate reduction by (3-blockers is partially caused by a block of the stimulating effect of catecholamines on the hyperpolarization activated current If (or Ih) in the sinoatrial (SA) node.3-7 Since (3-blockers also have negative inotropic and dromotropic effects that can reduce their usefulness and applicability in ischemic heart disease, drugs targeted at the pacemaker current If can possibly be superior in certain aspects.8 '9 Zatebradine (UL-FS 49) is a drug with a specific bradycardiac effect.10-13 It reduces heart rate in a frequency-dependent manner with little or no effect on inotropism, both in animal models'0-22 and in humans. [23][24][25][26][27][28] The substance reduces the increase in heart rate caused by (3-stimulation in a noncompetitive manner, without influencing the positive inotropic effect. '3'29 Heart rate reduction is caused by a direct effect on diastolic depolarization rate (DDR) (phase IV) of the SA node action potential.…”
mentioning
confidence: 99%